Advancing culture of living with landslides. Volume 4, - Mikoš, Matjaž; Casagli, Nicola; Yin, Yueping; Sassa, Kyoji (Springer, 2017)
This volume contains peer-reviewed papers from the Fourth World Landslide Forum organized by the International Consortium on Landslides (ICL), the Global Promotion Committee of the International Programme on Landslides (IPL), University of Ljubljana (UL) and Geological Survey of Slovenia in Ljubljana, Slovenia from May 29 to June 2, 2017. The complete collection of papers from the Forum is published in five full-color volumes. This fourth volume contains the following: " Earthquake-Induced Landslides " Rainfall-Induced Landslides " Rapid Landslides: Debris Flows, Mudflows, Rapid Debris-Slides " Landslides in Rocks and Complex Landslides: Rock Topples, Rock Falls, Rock Slides, Complex Landslides " Landslides and Other Natural Hazards: Floods, Droughts, Wildfires, Tsunamis, Volcanoes Prof. Matjaž Mikoš is the Forum Chair of the Fourth World Landslide Forum. He is the Vice President of International Consortium on Landslides and President of the Slovenian NationalPlatform for Disaster Risk Reduction. Prof. Nicola Casagli is Founding member of the International Consortium on Landslides(ICL), professor at the University of Florence and founder of the UNESCO Chair on geohydrological hazards at the same University. Prof. Yueping Yin is the President of the International Consortium on Landslides and the Chairman of the Committee of Geo-Hazards Prevention of China, and the Chief Geologist of Geo-Hazard Emergency Technology, Ministry of Land and Resources, P.R. China". Prof. Kyoji Sassa is the Founding President of the International Consortium on Landslides(ICL). He is Executive Director of ICL and the Editor-in-Chief of International Journal"Landslides" since its foundation in 2004. IPL (International Programme on Landslides) is a programme of the ICL. The programme is managed by the IPL Global Promotion Committee including ICL and ICL supportingorganizations, UNESCO, WMO, FAO, UNISDR, UNU, ICSU, WFEO, IUGS and IUGG. TheIPL contributes to the United Nations International Strategy for Disaster Reduction and the ISDR-ICL Sendai Partnerships 2015-2025.
Keywords: Landslides.; elektronické knihy; electronic books